2016
DOI: 10.1016/j.ijsu.2016.04.033
|View full text |Cite
|
Sign up to set email alerts
|

A surgeon-led model to improve operating theatre change-over time and overall efficiency: A randomised controlled trial

Abstract: This study demonstrates a statistically significant improvement in median change-over times using this model. This re-design can be implemented without incurring extra costs, staff, or operating theatres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 12 publications
0
22
1
Order By: Relevance
“…This protocol not only serves to clarify roles and educate OR team members on case details but signals to team members that the surgeon has thoroughly prepared and that guidance and leadership can be expected. The literature strongly supports this concept that surgeon‐led communication can alter OR dynamics and efficiency . A Johns Hopkins study examining preoperative briefings found that delays in care were reduced by up to 82% when a surgeon‐led 2‐minute standardized briefing was used immediately before the case .…”
Section: Discussionmentioning
confidence: 94%
“…This protocol not only serves to clarify roles and educate OR team members on case details but signals to team members that the surgeon has thoroughly prepared and that guidance and leadership can be expected. The literature strongly supports this concept that surgeon‐led communication can alter OR dynamics and efficiency . A Johns Hopkins study examining preoperative briefings found that delays in care were reduced by up to 82% when a surgeon‐led 2‐minute standardized briefing was used immediately before the case .…”
Section: Discussionmentioning
confidence: 94%
“…[4,12,13,[26][27][28][29][30] Factors influencing productivity and timeliness using the turnover time measure have been reported in numerous OR efficiency studies. [12,21,26,[31][32][33][34][35][36] As was noted in the Canadian Paediatric Surgical Wait Times Project, a lack of a standard methodology for measuring the outcomes in these studies limits the ability to benchmark externally. [4] While there is a plethora of literature focusing on OR efficiency, to our knowledge this is the first study using a matrix of four metrics to measure, benchmark and report monitor OR efficiency that can benchmark improvements over time.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of a single surgeon team-based work practice model translated into 58% reduction in median change-over time and no cancellations due to lack of time in the intervention group compared with 37 cancellations in the control group [13].…”
Section: Discussionmentioning
confidence: 99%